2012
DOI: 10.1007/s13760-012-0065-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dexamethasone on the frequency of postdural puncture headache after spinal anesthesia for cesarean section: a double-blind randomized clinical trial

Abstract: In this study, we evaluated the effect of dexamethasone used as a prophylaxis for nausea and vomiting on the incidence of postdural puncture headache (PDPH) in pregnant women receiving spinal anesthesia for cesarean section. In a prospective, randomized, double-blind, placebo-controlled study, 372 women under spinal anesthesia received 8 mg of dexamethasone or placebo intravenously just after the umbilical cord was clamped. The rate of PDPH and correlated risk factors were evaluated. The prevalence of nausea a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 19 publications
0
45
1
2
Order By: Relevance
“…The frequency rate of this headache in dexamethasone group was 10.8%, while this frequency in placebo group was 6.2% indicating a statistically significant difference. They finally arrived at the conclusion that using this medicine is a risk factor in occurrence of headaches after dura rupture (9). These results were not in line with those achieved in our study.…”
Section: Discussioncontrasting
confidence: 86%
See 2 more Smart Citations
“…The frequency rate of this headache in dexamethasone group was 10.8%, while this frequency in placebo group was 6.2% indicating a statistically significant difference. They finally arrived at the conclusion that using this medicine is a risk factor in occurrence of headaches after dura rupture (9). These results were not in line with those achieved in our study.…”
Section: Discussioncontrasting
confidence: 86%
“…These results were not in line with those achieved in our study. Dexamethasone has caused a noticeable reduction in headache scale following spinal anesthesia in our research, but Yousefshahi's results were completely different and had introduced dexamethasone as a risk factor for headaches caused by spinal anesthesia (9). The cause of difference is not clear, but the main point is that nearly all previous studies had confirmed the effectiveness of dexamethasone in reducing the headaches caused by spinal anesthesia.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…45 Yousefshashi et al also found a reduced incidence of PDPH with dexamethasone at 24 hours (p = 0.046) but this effect was lost by the second day. 46 Intravenous hydrocortisone 200 mg stat, followed by 100 mg three times daily for 48 hours was shown to be effective in reducing the severity of PDPH among a sample of obstetric patients. 47 Similar effectiveness of hydrocortisone was also demonstrated by Alam and colleagues among non-obstetric patients.…”
mentioning
confidence: 95%
“…Однак iншi автори з Iрану [6], якi вводили 8 мг дексаметазону внутрiшньовенно перед спiнальною анестезiєю для ортопедичних операцiй на нижнiх кiнцiвках, не виявили статистично значного зниження частоти головного болю, хоча його iнтенсивнiсть була нижчою пiсля дексаметазону. Навпаки, ще одна група дослiдникiв [19] з Тегерана (Iран) при внутрiшньовенному введеннi 8 мг дексаметазону одразу ж пiсля перетискання пуповини при кесаревiм розтинi пiд спiналь-ною анестезiєю не виявила зниження частоти пiсляоперайної нудоти та блювання, але виявила збiльшення частоти й iнтенсивностi головного болю.…”
Section: медикаментозна профIлактикаunclassified